Evaluation for the Phytoconstituents, Phytochemical & Pharmacological Investigations of Diospyros malabarica (Desrousseaux) Available in Bangladesh - Afnan Sayeid Himi; Manik Pramanik; Maisha Muntaher; Md. Sagar Mia; Md. Ariful Islam; Khadizatul Kubra; Khandaker Antara Anika (Medical Science: Trends and Innovations Vol. 13, 2025)
Diospyros malabarica is a prominent member of the Ebenaceae. In Assamese, this medium-sized evergreen tree is referred to as kendu. Many North-East Indian ethnic groupings use the herb for its ethnomedical purposes. The following parts of Diospyros malabarica were used to screen phytochemicals both qualitatively (flavonoids, terpenoids, saponins, tannins) and quantitatively (total phenolic and flavonoid contents). All the parts of Diospyros malabarica were extracted in turn using organic solvents like petroleum ether, dichloromethane, ethyl acetate, ethanol, methanol and water in decreasing order of polarity from less polar to more polar solvents. These solvents included the root, leaves, bark, stem, ripe and unripe fruit. Additionally, biological activities that have antibacterial, antifungal, anticancer, antidiabetic and anti-inflammatory properties were investigated. The results showed that methanol was the best solvent for the extraction, followed by ethanol. It represented the highest extraction yield (18.3%), the richest diversity of phytochemicals and the highest levels of total phenolic and flavonoid contents in bark extract (602 ± 0.001 \(μ\)g EAG/mg of extract and 455 ± 0.6 \(μ\)g EQ/mg of extract, respectively). Among various D. malabarica extracts, methanol bark extract had the highest in vitro antibacterial activity (30.25 mm ± 0.9), antifungal activity (18.25 mm ± 0.2), anticancer activity (48%), antidiabetic activity (68%) and anti-inflammatory activity (62%). For this reason, among other extracts of D. malabarica, methanol may be the best solvent to extract the most phytochemicals, promising antioxidants and in vitro biological activities from the bark extract. It may also act as a free radical rummager.